Russia and the Conception of “Pivot to Asia” - A. Lukin; I. Denisov (Международная аналитика)
The article deals with the pivot to Asia started in the USA in 2011, now becoming a part of US military strategy. Asian-Pacific region will be playing increasingly important role in securing of political, economic and defence interests of the USA seeking to consolidate world order based on “American leadership from the position of strength” – which is the main principle of New National Security Strategy. Pivot to Asia is understood as modernization and reinforcement of traditional “security alliances”. The old policy of “deterrence” of China as main geopolitical competitor is still being pursued.Military presence of the USA on Japanese islands is used for rearmament of Japanese self-defence forces. New bilateral treaty is being prepared, thus creating the possibility of joint actions of armed forces of Japan and US on the territories in- and outside Pacific region. Threat for North Korea is used as a good pretext for build-up of US military forces and deployment of THAAD complexes on the territory of South Korea. China and Russia express same attitude in this respect regarding THAAD as an instrument for increase tension in the region. Defence co-operation between Australia and US has incentives for development as well as limitations: Australia is not sure US are able to fulfill its obligations in case of crisis and at the same time economic co-operation with Beijing is of crucial interest for Australia. The involvement of Philippines in the territorial dispute with China made possible for US to strengthen cooperation in the sphere of defence. After power shift in Thailand military cooperation with US stopped. Seeking new partners in the region, US is lifting embargo to supply of weapons to Vietnam and gradually unfreezing relations with Myanmar. US moves in SEA can be regarded as reaction to Chinese promotion of “Maritime silk route of the 21st century” concept. Relations with India are viewed in the USA as means of deterrence of China ambitions and competition with Russia in military co-operation.The article contains practical recommendations how Russia should act when purpose of increasing its influence in the region is on the agenda.